Emergence of tick-borne diseases at northern latitudes in Europe: a comparative approach. Issue 1 (December 2017) - Mysterud, Atle; Jore, Solveig; Østerås, Olav; Viljugrein, Hildegunn
Abstract The factors that drive the emergence of vector-borne diseases are difficult to identify due to the complexity of the pathogen-vector-host triad. We used a novel comparative approach to analyse four long-term datasets (1995–2015) on the incidence of tick-borne diseases in humans and livestock (Lyme disease, anaplasmosis and babesiosis) over a geographic area that covered the whole of Norway. This approach allowed us to separate general (shared vector) and specific (pathogen reservoir host) limiting factors of tick-borne diseases, as well as the role of exposure (shared and non-shared pathogens in different hosts). We found broadly similar patterns of emergence across the four tick-borne diseases. Following initial increases during the first decade of the time series, the numbers of cases peaked at slightly different years and then stabilized or declined in the most recent years. Contrasting spatial patterns of disease incidence were consistent with exposure to ticks being an important factor influencing disease incidence in livestock. Uncertainty regarding the reservoir host(s) of the pathogens causing anaplasmosis and babesiosis prevented a firm conclusion regarding the role of the reservoir host-pathogen distribution. Our study shows that the emergence of tick-borne diseases at northern latitudes is linked to the shared tick vector and that variation in host-pathogen distribution and exposure causes considerable variation in emergence.